Identification of three movement phases of the hand during lateral and pulp pinches using video motion capture - Jahn, Johanna (Springer-Verlag, 2013)
BACKGROUND: Hand injuries affect a person’s ability to engage successfully in activities of daily living (ADLs). Video motion capture (VMC) facilitates measurement of dynamic movement. No study to date has used VMC as a means of quantifying the simultaneous movement patterns of all joints of all digits of the hand during active purposeful movement. METHOD: The purpose of this study was to analyze all joints of all five digits during active completion of the lateral and pulp pinches. VMC data were collected from four participants during completion of two pinches. Joint angles were plotted to facilitate identification of movement patterns. RESULTS: Range of motion recorded in all joints with VMC, excluding flexion of the thumb carpometacarpal of both pinches, coincided with the normative goniometric data. Three phases were observed: initiation, preshaping, and pinch phases. Patterns of movement in all digits were identified for the two pinches. CONCLUSION: VMC is a feasible and valid method for objectively quantifying dynamic movement of multiple joints simultaneously. The results provide new insight to the dynamics of hand movement as well as a basis for subsequent evaluations of movement patterns performed in ADLs and instrumental ADLs.